Hayek versus Marx :and today's challenges - Aarons, Eric (Routledge frontiers of political economy, 2009)
The aim of the book is to stimulate the realignment of political, theoretical and philosophical thinking that is now beginning in response to global warming. The author provides an examination of the theories of the most prominent social philosophers of the 19th and 20th centuries – Karl Marx and Friedrich Hayek. He does so in the belief that the work of these two thinkers, in their commonalities and differences, successes and failures, contain important indicators of the content of a social philosophy suited to today’s conditions.